The injur'd husband, or, The mistaken resentment ; and Lasselia, or, The self-abandon'd - Haywood, Eliza Fowler, 1693?-1756 (Eighteenth-century novels by women., 1999)
Eliza Haywood (1693?-1756) was one of the first women in England to earn a living writing fiction. Her early tales of amorous intrigue, sometimes based on real people, were exceedingly popular though controversial. Haywood, along with her contemporary Daniel Defoe, did more than any other writer to create a market for fiction in the period just prior to the emergence of Samuel Richardson, Henry Fielding, and Tobias Smollett, the dominant novelists of the mid-eighteenth century. The scheming, sexually predatory anti-heroine of The Injur'd Husband is a memorable villain who defies all expectatio.